2017
DOI: 10.1093/pcp/pcx082
|View full text |Cite
|
Sign up to set email alerts
|

The Tonoplast-Localized Transporter MTP8.2 Contributes to Manganese Detoxification in the Shoots and Roots of Oryza sativa L.

Abstract: Manganese (Mn) cation diffusion facilitators (Mn-CDFs) play important roles in the Mn homeostasis of plants. In rice, the tonoplast-localized Mn-CDF metal tolerance protein 8.1 (MTP8.1) is involved in Mn detoxification in the shoots. This study functionally characterized the Mn-CDF MTP8.2 and determined its contribution to Mn tolerance. MTP8.2 was found to share 68% identity with MTP8.1 and was expressed in both the shoots and roots, but its transcription level was lower than that of MTP8.1. Transient expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 34 publications
2
50
0
Order By: Relevance
“…OsMTP8.1 was highly expressed in older leaves, and it was induced and repressed by high and low Mn 2+ levels, respectively (Chen et al, 2013). OsMTP8.2 was expressed in roots and shoots, and it showed lower expression levels than OsMTP8.1 (Takemoto et al, 2017). The mtp8.1mtp8.2 double mutant suffered from necrotic leaf blades.…”
Section: Vacuoles As Manganese Storesmentioning
confidence: 99%
“…OsMTP8.1 was highly expressed in older leaves, and it was induced and repressed by high and low Mn 2+ levels, respectively (Chen et al, 2013). OsMTP8.2 was expressed in roots and shoots, and it showed lower expression levels than OsMTP8.1 (Takemoto et al, 2017). The mtp8.1mtp8.2 double mutant suffered from necrotic leaf blades.…”
Section: Vacuoles As Manganese Storesmentioning
confidence: 99%
“…4 Knockout of MTP8.1 resulted in significant growth reduction in addition to chlorosis and necrosis in leaves under high Mn conditions, 3 whereas no obvious Mn toxicity symptoms were presented in mtp8.2 leaves. 4 However, when MTP8.2 was knocked down in mtp8.1, the mutants (mtp8.2i/mtp8.1) exhibited higher Mn sensitivity than did mtp8.1, 4 indicating that MTP8.2 is also important for Mn tolerance in shoots. In roots, MTP8.1 and MTP8.2 were expressed at similar levels regardless of Mn condition.…”
Section: Metal Tolerance Protein; Cation Diffusion Facilitator; Transmentioning
confidence: 96%
“…2 We recently reported that Mn in old leaves is detoxified by two vacuolar transporters, MTP8.1 and MTP8.2. 3,4 Both MTP8.1 and MTP8.2 are constitutively expressed at higher levels in old than in young leaves, but the level of MTP8.1 is several times higher than that of MTP8.2. 4 Knockout of MTP8.1 resulted in significant growth reduction in addition to chlorosis and necrosis in leaves under high Mn conditions, 3 whereas no obvious Mn toxicity symptoms were presented in mtp8.2 leaves.…”
Section: Metal Tolerance Protein; Cation Diffusion Facilitator; Transmentioning
confidence: 99%
See 2 more Smart Citations